Examination and analysis of modern scintigraphic methods with reference to diagnostic procedures that predict disease risks - Manjenčić, Darko; Cvjetković, Jovana; Manjenčić, Anja; Mićić, Vladan; Gmajnić, Rudika; Baškot, Branislav (PONS - medicinski časopis, 2026)
Nuclear medicine is a specialized, relatively young branch of medicine that uses radioactive compounds for diagnostic and therapeutic purposes. The basis of the application of radiolabels and radiolabeled substances in nuclear/medical diagnostics is the ability to monitor physiological and pathophysiological processes in the body. Radiopharmaceuticals are radioactively labeled chemical compounds, consisting of a radioactive isotope and a carrier molecule, which has a high degree of specificity for the process under investigation. In diagnostics, 99mTc has been indisputable for decades, due to its excellent physical properties, high quality and easy availability, and the main source for obtaining it is chromatographic 99Mo/99mTc generators. Scintigraphy is an imaging diagnostic procedure that monitors and records the distribution of the radioactivity of the applied radiopharmaceutical, obtaining a scintigram, a two-dimensional image, while single photon emission computed tomography (SPECT) represents the circular motion of the detector around the body, along with a three-dimensional view of the organs. which can be observed in sections, in three planes (sagittal, frontal and transverse), where it is shown more clearly and precisely localizes any pathological process. In this work, we used a gamma camera Diacam - Siemens, penultimate generation, with extraordinary uniformity and resolution of the obtained diagnostic image. Based on the study reports of perfusion scintigraphy of the myocardium - mibi stress and scintigraphy of the parathyroid glands, made with 99mTc - sestamibi, we came to the images, which were studiously analyzed and processed with the help of a special computer program. We obtained a completely normal finding of the heart muscle, while the planar images of the neck and mediastinum were also disease-free, with a weakened display of radiopharmaceutical accumulation. From the perspective of the importance of scintigraphies performed, in the domain of image diagnostics, the paper shows the exceptional quality of the images obtained. Scintigraphy of the parathyroid glands is crucial in detecting disorders of the parathyroid glands, and also serves as a preoperative method. Nuclear medicine is the fastest growing medical field. It is extremely effective and with few side effects, allowing elderly patients to prolong and have a higher quality of life, compared to conventional treatments, such as chemotherapy. It is very versatile and is used in the treatment of various types of cancer.
Keywords: Nuclear medicine, Radiopharmaceuticals, Scintigraphy, SPECT/CT, Technetium